The effect of stress and workload on employee performance in the division maintenance department PT Indominco Mandiri In Bontang - Utari, Tri; Wediawati, Tuti; Althalets, Fareis (Technium Social Sciences Journal, 2021)
This experiment was conducted to test and analyze the effect of stress and workload partially and simultaneously on the performance of employees in the maintenance department at PT Indominco Mandiri, Bontang City. The sample used is 45 respondents who are employees of the maintenance department at PT Indominco Mandiri in Bontang. Data analysis used multiple linear regression equations and hypothesis proofing through t-test, F test and coefficient of determination (R2) and dominant test. The results of the t-test of the work stress variable are the t-count value of 3.540 2.018 and a significance value of 0.001 0.05, which means that work stress has a significant effect on employee performance. The results of the t-test of the workload variable are the t-count value of 2.706 2.018 and a significance value of 0.010 0.05, meaning that the workload has a significant effect on employee performance. The statistical test results (F test) are 6.168 0.311 and a significance value of 0.004 0.05, meaning that simultaneously stress and workload have a significant effect on the performance of employees in the maintenance department at PT Indominco Mandiri in Bontang. The dominant test results show that the work stress variable has a dominant effect on employee performance. So, it can be concluded that the work stress variable has the most significant influence on the performance of employees in the maintenance department at PT Indominco Mandiri in Bontang. So, it can be suggested that the order flow should be by the structure not to confuse employees. Furthermore, the company should pay special attention to employees who feel they have conflicts that interfere with work; then, the company should change shifts or transfer employees to reduce the monotony experienced by employees, and this research still has shortcomings. Therefore, it is recommended for further researchers to improve by adding other variables that can improve employee performance.